Human Wharton's Jelly Stem Cell (hWJSC) Extracts Inhibit Ovarian Cancer Cell Lines OVCAR3 and SKOV3 in vitro by Inducing Cell Cycle Arrest and Apoptosis - Kalamegam, Gauthaman; Sait, Khalid Hussein Wali; Ahmed, Farid; Kadam, Roaa; Pushparaj, Peter Natesan; Anfinan, Nisreen; Rasool, Mahmood; Jamal, Mohammad Sarwar; Abu-Elmagd, Muhammed; Al-Qahtani, Mohammed (Frontiers in Oncology, 2018)
Ovarian cancer is a highly lethal and the second highest in mortality among gynaecological cancers. Stem cells either naïve or engineered are reported to inhibit various human cancers in both in-vitro and in-vivo. Herein we report the cancer inhibitory properties of human Wharton’s jelly stem cell (hWJSC) extracts, namely its conditioned medium (hWJSC-CM) and cell lysate (hWJSC-CL) against two ovarian cancer cell lines (OVCAR3 and SKOV3) in-vitro. Cell metabolic activity assay of OVCAR3 and SKOV3 cells treated with hWJSC-CM (12.5, 25, 50, 75, 100%) and hWJSC-CL (5, 10, 15, 30, 50µg/ml) demonstrated concentration dependent inhibition at 24h-72h. Morphological analysis of OVCAR3 and SKOV3 cells treated with hWJSC-CM (50, 75, 100%) and hWJSC-CL (15, 30, 50µg/ml) for 24h-72h showed cell shrinkage, membrane damage/blebbings and cell death. Cell cycle assay demonstrated an increase in the sub-G1 and G2M phases of cell cycle following treatment with hWJSC-CM (50, 75, 100%) and hWJSC-CL (10, 15, 30µg/ml) at 48h. Both OVCAR3 and SKOV3 cells demonstrated mild positive expression of activated caspase 3 following treatment with hWJSC-CM (50%) and hWJSC-CL (15µg/ml) for 24h. Cell migration of OVCAR3 and SKOV3 cells were inhibited following treatment with hWJSC-CM (50%) and hWJSC-CL (15µg/ml) for 48h. Tumour spheres (TS) of OVCAR3 and SKOV3 treated with hWJSC-CM (50, 75, 100%) and hWJSC-CL (10, 15, 30µg/ml) for 48h showed altered surface changes including vacuolations and reduction in size of TS. TS of OVCAR3 and SKOV3 also showed the presence of few ovarian cancer stem cells (CSCs) in minimal numbers following treatment with hWJSC-CM (50%) or hWJSC-CL (15µg/ml) for 48h. Real-time gene expression analysis of OVCAR3 and SKOV3 treated with hWJSC-CM (50%) or hWJSC-CL (15µg/ml) for 48h demonstrated decreased expression of cell cycle regulatory genes (cyclin A2, Cyclin E1), prostaglandin receptor signaling genes (EP2, EP4) and the pro-inflmmatory genes (IL-6, TNF-α) compared to untreated controls. The results indicate that hWJSC-CM and hWJSC-CL inhibit ovarian cancer cells at mild to moderate levels by inducing cellular changes, cell cycle arrest, apoptosis, decreasing the expression of CSC markers and related genes regulation. Therefore, the stem cell factors in hWJSCs extracts can be useful in cancer management.